Kajian Tingkat Pelayanan dan Aksesibilitas Fasilitas Difabel di Stasiun Kertosono Berdasarkan Metode IPA - Anggraini, Ririn; Utomo, Nugroho; Alfiansyah, Achmad Dzulfiqar (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Kertosono Station is one of the major railway stations located in Nganjuk Regency, East Java, serving as an important transit point for intercity travel on the southern route of Java Island. Accessibility in public facilities, such as railway stations, is a crucial issue to support the mobility of persons with disabilities. This study aims to evaluate the service level and availability of facilities for persons with disabilities at Kertosono Station in accordance with the “Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 63 of 2019”. The research method used includes observation, which involves assessing the compliance of disability facility standards at Kertosono Station, and a questionnaire distributed to passengers and visitors who are currently at or have previously visited Kertosono Station. The measurement used is Importance Performance Analysis (IPA), which maps service attributes into four quadrants to determine improvement priorities. The analysis results using the IPA method show that several attributes fall into Quadrant I. These attributes include the availability of a designated waiting area with priority seating, male and female toilets as well as a special toilet for persons with disabilities, and a dedicated path for wheelchairs leading to the train. This indicates that Kertosono Station still requires improvements in priority aspects to support more inclusive and comfortable public services for persons with disabilities as well as all passengers.